How to find RNA thermometers - Righetti, Francesco; Narberhaus, Franz (Frontiers in Cellular and Infection Microbiology, 2014)
Temperature is one of the decisive signals that a mammalian pathogen has entered its warm-blooded host. Among the many ways to register temperature changes, bacteria often use temperature-modulated structures in the untranslated region of mRNAs. In this article, we describe how such RNA thermometers (RNATs) have been discovered one by one upstream of heat shock and virulence genes in the past, and how next-generation sequencing approaches are able to reveal novel temperature-responsive RNA structures on a global scale.